1997
DOI: 10.1021/ja971110h
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Epothilones A and B via a Macrolactonization-Based Strategy

Abstract: The total syntheses of epothilones A (1) and B (2) and several analogues thereof are described. The reported strategy relies on a macrolactonization approach and features selective epoxidation of the macrocycle double bond in precursors 3 and 4 (Scheme ), respectively, as well as high convergency and flexibility. Building blocks 9−12 and 15 were constructed by asymmetric processes and coupled via Wittig, aldol, and macrolactonization reactions to afford the basic skeleton of epothilones and that of several of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0
9

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(135 citation statements)
references
References 40 publications
6
120
0
9
Order By: Relevance
“…N- -oxazolidinone 23 was selectively methylated to give 24, thus establishing the desired tate. The final coupling steps follow the procedure employed by Nicolaou et al [11] in their total synthesis of epostereochemistry. Reduction with LiAlH 4 [10] and subsequent oxidation generated the required (2S)-methyl-6-heptenoic thilone A (1) (Scheme 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N- -oxazolidinone 23 was selectively methylated to give 24, thus establishing the desired tate. The final coupling steps follow the procedure employed by Nicolaou et al [11] in their total synthesis of epostereochemistry. Reduction with LiAlH 4 [10] and subsequent oxidation generated the required (2S)-methyl-6-heptenoic thilone A (1) (Scheme 9).…”
Section: Resultsmentioning
confidence: 99%
“…TBS triflate and 2,6-lutidine in dichloromethane. duced at the end of this reaction sequence, to make this Selective deprotection of the primary ether with CSA [11] in sequence suitable for the introduction of different heteromethanol followed by DessϪMartin oxidation of the result-cyclic side chains in a combinatorial manner. ant alcohol 33 completed the synthesis of aldehyde 3.…”
Section: Resultsmentioning
confidence: 99%
“…A better strategy for this total synthesis includes the formation of the (Z)-alkene on a linear precursor, and a macrolactonization to close the 16-membered ring. [28] Another study concerning the influence of remote substituents was reported by Fürstner et al in the course of their approach towards the synthesis of salicylihalamides A and B (Scheme 9). [29] The free phenol 21 a, in the presence of catalyst 10 in toluene at 80 8C, furnished the Z isomer of 22 a exclusively.…”
Section: Effect Of Substrate Substituentsmentioning
confidence: 98%
“…Compound 10 was synthesized as reported earlier. [32] Selective reduction of the aldehyde group of 10 with NaBH 4 gave the primary alcohol 11 as a mixture with its hemiacetal 12, and was converted to the bis-silyl ether 4 with TBSCl and imidazole.…”
Section: Resultsmentioning
confidence: 99%